Effectiveness of histopathological examination in medicolegal autopsies – A four-year retrospective study from a tertiary level medical college hospital from South India - Devi Chaganti, Padmavathi; Konkay, Kaumudi; Devi Karri , Maruthi (Journal of Indian Academy of Forensic Medicine, 2021)
Histopathological examination (HPE) in medicolegal autopsies (MLA) is essential when gross examination is not sufficient to  confirm or exclude morphological changes at cellular level. This study aims to evaluate the histopathological findings in medicolegal  autopsies and determine the efficacy and effectiveness of HPE in MLA. A four years retrospective study was done from July 2015 to  June 2019 and all cases of MLA which were sent for HPE to department of pathology were included in the study and clinical  autopsies were excluded from the study. There were total of 364 cases with age range was between 0 to 86 years, with male female  ratio of 1:1.09. Majority of the cases sent for HPE were for suicidal deaths by hanging which accounted 80.4% (293 out of 364 cases).  Of autopsies done for cases other than suicidal hanging and strangulation, which were 63 cases, the most frequent organ submitted  was heart (38 cases), followed by lungs (22 cases), liver(18 cases), kidneys (17 cases), brain ( 14 cases), spleen (13 cases), uterus ( 8  cases), intestine (6 cases), testes ( 2cases), pancreas and gall bladder (one case each). Overall significant findings were noted in any of  the organs in 41 cases, did not show significant changes on microscopy in 7 cases, and showed autolysis in 15 cases. In our study  HPE was more efficient in Lung (72.9%), followed by heart (36.3%). HPE plays an important role in establishing cause of death in  MLA. It will be more fruitful when autopsy surgeon and histopathologist work together and autopsy surgeon clearly specifies what he  is expecting or what he wants to exclude.
Keywords: Medicolegal autopsies; Gross findings; Histopathology; Suicidal hanging